Multi-criteria approach to passive space design in buildings: Impact of courtyard spaces on public buildings in cold climates. (July 2015) - Song, Yehao; Li, Junjie; Wang, Jialiang; Hao, Shimeng; Zhu, Ning; Lin, Zhenghao
Abstract: Passive design has widely been identified to be one of the most economical and effective strategies for sustainable building. However, the research on verification of passive design strategies is in its initial stages. Currently, its test method and verification conclusions are not sufficiently scientific to validate. This study introduces a new logical framework to assess building space performance. A multi-criteria approach has been developed to validate and optimize the influence of passive spaces on sustainable buildings from the perspectives of building environment quality and occupant satisfaction. Building environment quality was judged by fieldwork physical environment tests, including indoor thermal, lighting, indoor air quality and acoustics data in the operating phase. A voting method designed to test satisfaction was developed to evaluate the occupants' satisfaction with the building's overall environment and space efficiency. Considering both the relationship between the building and people, and the building and the environment, from the dual perspectives of building design and building environment control, a comprehensive judgment model for a Comfort – Satisfaction Matrix was developed to display the regulation capacity of the building's environmental performance in the passive space. Finally, an in-depth fieldwork survey of six types of passive courtyard spaces in cold climates was conducted as an example to validate the developed multi-criteria approach. The results indicate the level of environmental performance of each object building, and highlight optimized possibilities for passive space and the whole building in the design and renovation phases. Graphical abstract: Highlights: Establishment of a new logical framework to assess passive space performance. Development of software to display environmental test data distribution clouds. Development of a semantic differential method to judge occupant satisfaction. Distribution of a comprehensive judgment model of the Comfort – Satisfaction Matrix.